Acute Rheumatic Fever: Findings of a Hospital-Based Study and an Overview of Reported Outbreaks - Upton D Allen; Michael Braudo; Stanley E Read (Canadian Journal of Infectious Diseases)
To review the characteristics of reported outbreaks of acute rheumatic fever in the United States, and to determine if there is an increase in the incidence of acute rheumatic fever in the population served by the Hospital for Sick Children, Toronto, Ontario, the authors conducted a literature search and a retrospective review of inpatients and outpatients, satisfying the revised Jones criteria for the diagnosis of acute rheumatic fever, from 1972 to 1988. Patients satisfying the revised Jones criteria for the time period 1972–88 were included in the study. There have been eight articles reporting an increase in acute rheumatic fever in the United States. In three, the majority of children were white and from middle class suburban/rural communities in different geographic locations. Mucoid strains of group A streptococci were implicated but not confirmed as being associated with the outbreaks in three. The results of the chart review at the Hospital for Sick Children revealed that 83 cases satisfied the revised Jones criteria. The number of cases per 100,000 children (aged 18 years or less) per year, decreased progressively over the study period. Polyarthritis was the most frequently seen major criterion occurring in 73% of patients (61 of 83). The most frequently affected ethnic groups were Italians 23%, Afro-Canadians 19% and Orientals 8%. The reported outbreaks in the United States are multifocal and predominantly confined to white middle class children residing in suburban/rural communities. There was no evidence of an increase in the number of cases of acute rheumatic fever seen in the population served by the Hospital for Sick Children; there was a progressive decline in number of cases over the study period. The results facilitate the characterization of acute rheumatic fever within North America into three different patterns of occurrence.